Literasi Digital Dalam Mendukung Digital Society Menuju Desa Cerdas Melalui Pendidikan Karakter Pada Karang Taruna Desa Mlese - Mutiatul Astna; Anita Trisiana; Nur Azizah (Politeknik Piksi Ganesha Indonesia, 2025)
This research analyzes the role of digital literacy in supporting the formation of a digital society towards smart villages through character education in youth organizations (karang taruna). In this context, digital literacy is not only seen as a technical skill but also as a tool for building strong character values among young people. The study examines various dimensions of digital literacy, including the ability to evaluate information, communicate effectively, and utilize technology for collaboration and innovation. Using a qualitative approach, the research involves surveys and interviews with members of karang taruna and local stakeholders to identify best practices in integrating character education with digital literacy. This study aims to demonstrate how character education among karang taruna can be strengthened through the use of digital technologies, such as social media and online learning platforms. Karang taruna is expected to play a key role in creating an adaptive and innovative community while achieving sustainable development goals at the village level.